Sosialisasi Peraturan Daerah Dalam Rangka Optimalisasi Fungsi Legislasi Anggota Dprd Provinsi Riau (Studi Pelaksanaan Sosialisasi Peraturan Daerah di Masa Pandemi Covid 19) - Sadriah Lahamit (UIR Press, 2021)
The main duties and functions of DPRD are expressly contained in Law number 23 of 2014 concerning Regional Government, This task is spelled out in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number. 80 of 2015 concerning the Formation of Regional Legal Products, article 163 paragraph (1) The dissemination of regional regulations that have been promulgated is carried out jointly by the regional government and the DPRD. The form of activities carried out is the Socialization of Riau provincial regulations in their constituency. Public policies that are made in the form of regional regulations are expected to meet the public needs of the community. For this reason, it requires the authority to make public policies, with the concept of decentralization, regional government can make public policies according to the needs of the local community, for this, the province of Riau. Regional regulations that have been passed together with the DPRD and the Provincial Government need to be conveyed to the public as a form of responsibility that the public needs submitted to the government have been made a legal basis for its implementation in the form of the Riau Provincial Regional Regulation. It is hoped that the socialization of regional regulations that is delivered is expected to be understood and beneficial to the community, therefore the form of political communication that is carried out must be in accordance with the people in the electoral district.